One‐year efficacy and safety of saxagliptin add‐on in patients receiving dapagliflozin and metformin. Issue 11 (19th August 2016) - Matthaei, S.; Aggarwal, N.; Garcia‐Hernandez, P.; Iqbal, N.; Chen, H.; Johnsson, E.; Chin, A.; Hansen, L.
Abstract : Aims: Greater reductions in glycated haemoglobin (HbA1c) with saxagliptin, a dipeptidyl peptidase‐4 inhibitor, versus placebo add‐on in patients with type 2 diabetes who had inadequate glycaemic control with dapagliflozin 10 mg/d plus metformin were demonstrated after 24 weeks of treatment. Results over 52 weeks of treatment were assessed in this analysis. Materials and methods: Patients (mean baseline HbA1c 7.9%) receiving open‐label dapagliflozin 10 mg/d plus metformin were randomized to double‐blind saxagliptin 5 mg/d or placebo add‐on. Results: The adjusted mean change from baseline to week 52 in HbA1c was greater with saxagliptin than with placebo add‐on −0.38% vs 0.05%; difference −0.42% (95% confidence interval −0.64, −0.20)]. More patients achieved the HbA1c target of <7% with saxagliptin than with placebo add‐on (29% vs 13%), and fewer patients were rescued or discontinued the study for lack of glycaemic control with saxagliptin than with placebo add‐on (19% vs 28%). Reductions from baseline in body weight (≤1.5 kg) occurred in both groups. Similar proportions of patients reported ≥1 adverse event with saxagliptin (58.2%) and placebo add‐on (58.0%); no new safety signals were detected. Hypoglycaemia was infrequent in both treatment groups (≤2.5%), with no major episodes. The rate of urinary tract infections was similar in the saxagliptin and placebo add‐on groups (7.8% vs 7.4%). The incidence of genital infections was 3.3% with saxagliptin versus 6.2% with placebo add‐on. Conclusions: Triple therapy with saxagliptin add‐on to dapagliflozin plus metformin for 52 weeks resulted in sustained improvements in glycaemic control without an increase in body weight or increased risk of hypoglycaemia.